Mobile-based Expert System for Selecting Broiler Farm Location Using PostGIS - Arif Kurnia Wijayanto; Kudang Boro Seminar; Rudi Afnan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Massive development of broiler farms has led to many socio-environmental problems. Based on idea that broiler farm must be located at suitable location, an expert system for site selection based on the socio-environmental factors and sustainable principles is urgently needed to cope with this problem. The objective of this research was to develop a mobile-based expert system as a guidance for broiler farmers to choose best location for broiler farm. There were four factors considered in the system: 1) ecology and environmental impact, 2) economic and infrastructure, 3) natural condition, and 4) natural disaster vulnerability, each of which consists of sub-factors. A mobile-based expert system has been developed by using opensource web GIS server and PostgreSQL/PostGIS, and can be installed on Android device. As conclusion, a mobile-based expert system has been developed and can be used to determine suitable location for broiler farm development.